Interaksi Pendengar dan Promosi Program Siaran Radio “Polemik Trijaya” di Twitter - Taufik R. Talalu; Femalia Valentine (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The radio listener's comments and questions in weekend talk show broadcasting program entitled “Polemik Trijaya” were delivered via Twitter, which is also used to promote the program. This methodological study was determined to describe the broadcasting program's interaction and promotion in Twitter by studying the phenomenon in this research. The data was collected with interview, observation, and documentation techniques to be analyzed and concluded later on. It was found that the interactions used retweet and hashtag features, in which the hashtags used were specifically meant for the program topic which allows the interactions to continue even if the broadcasting program is ended. Twitter itself is an effective media to promote the “Polemik Trijaya” due to the promotional content that can be repackaged to be more interactive, the interactions are included in promotional content that can attract the interest of advertisers as a contributive element to the operational continuity of MNC Trijaya.